2011
DOI: 10.1021/jp207495r
|View full text |Cite
|
Sign up to set email alerts
|

Existence of a New Emitting Singlet State of Proflavine: Femtosecond Dynamics of the Excited State Processes and Quantum Chemical Studies in Different Solvents

Abstract: Proflavine (3,6-diaminoacridine) shows fluorescence emission with lifetime, 4.6 ± 0.2 ns, in all the solvents irrespective of the solvent polarity. To understand this unusual photophysical property, investigations were carried out using steady state and time-resolved fluorescence spectroscopy in the pico- and femtosecond time domain. Molecular geometries in the ground and low-lying excited states of proflavine were examined by complete structural optimization using ab initio quantum chemical computations at HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 46 publications
3
33
1
Order By: Relevance
“…All of the kinetic curves start with negative signals ( < 0), which gradually decrease to the positive values, remain constant, or further increase depending on the spectral range (460–480 nm, 500–520 nm, and 530–620 nm, respectively). These relatively long changes are described by the characteristic times in the range of 20 to 30 ps and can be attributed to solvent reorganization phenomena, frequently observed for different organic molecules in protic solvents [ 25 , 26 , 27 , 28 ]. The largest values of the first emerged subpicosecond negative signals were observed in the short wavelength range ( ≤ 550 nm, Figure 4 a,b) and are, presumably, associated with the dominant role of optical gain from the unrelaxed first excited state S 1 along with some possible input from the SA of the ground state S 0 .…”
Section: Resultsmentioning
confidence: 99%
“…All of the kinetic curves start with negative signals ( < 0), which gradually decrease to the positive values, remain constant, or further increase depending on the spectral range (460–480 nm, 500–520 nm, and 530–620 nm, respectively). These relatively long changes are described by the characteristic times in the range of 20 to 30 ps and can be attributed to solvent reorganization phenomena, frequently observed for different organic molecules in protic solvents [ 25 , 26 , 27 , 28 ]. The largest values of the first emerged subpicosecond negative signals were observed in the short wavelength range ( ≤ 550 nm, Figure 4 a,b) and are, presumably, associated with the dominant role of optical gain from the unrelaxed first excited state S 1 along with some possible input from the SA of the ground state S 0 .…”
Section: Resultsmentioning
confidence: 99%
“…The second time constant s 2 varies from 50 to 215 ps depending on the solvent. 27 We studied proavine-TEA and proavine-DMA as donoracceptor couples in different solvents of varying dielectric constants in a femtosecond-picosecond time-resolved uorescence set-up. Our previous studies showed that the addition of TEA to proavine increases its lifetime from 4.45 ns to 5.00 ns in ethanol.…”
Section: Resultsmentioning
confidence: 99%
“…The observed decay times are presumably due to the emission from the close lying singlet excited states ( 1 A 1 and 1 B 2 ) of proavine in homogeneous media and the variation in s 2 is due to the variation in Stokes shi and uorescence quantum yield of the dye with solvent polarity. 27 By considering the preferential residence of DMA and PF + molecules in different regions of the CTAB micelle, it could be inferred that the PF + molecules are repelled by its positively charged head groups and go into the water phase and thus cannot access the DMA molecules located in the hydrophobic tail region. 23 Due to the preferential residence of DMA molecules in the micellar core environment, probably the lone pair of nitrogen of this tertiary amine becomes protonated by the nearby NH 4 + group of the CTAB micelle, which is impossible in the case of TEA since it easily diffuses into the water phase owing to its small size and hydrophilicity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dye molecules were measured either in various solvents in quartz cuvette, or incorporated in zeolite LTL by suspending dyes/zeolite LTL in chloroform ($ 1 mg in 100 mL). [20][21][22]. The absorption and emission bands of AF at different concentrations in K-LTL are shown in Figs.…”
Section: Physical Measurementsmentioning
confidence: 99%